2012
DOI: 10.1002/jobm.201100460
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of phenol by using free and immobilized cells of Acinetobacter sp. BS8Y

Abstract: Strain BS8Y with high biodegradation activity and high tolerance of phenol was isolated from activated sludge in an insulating material plant of China. This strain was capable of removing 99.2% of the initial 600 mg/l phenol in liquid minimal medium within 24 h and tolerating phenol at concentrations of up to 1,200 mg/ml. DNA sequencing and homologous analysis of the 16S rRNA gene identified that the strain BS8Y belonged to an Acinetobacter species. Polyvinyl alcohol was used as gel matrix to immobilize the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…At the end of the experiment, phenol was removed for 100.00 and 7.30% from the tests at the phenol concentrations of 10 and 100 mg/L, respectively. Some previous works found that bacterial cultures could use phenol as a growth substrate even up to concentrations of 10,000 mg/L [6], [9], [10]. In this study, based on the result of the test at the phenol concentration of 10 mg/L, it is clear that AS could degrade and use phenol as a sole carbon source similar to the previous work [6], [9], [10].…”
Section: A Potential Of Phenol Removal By Assupporting
confidence: 80%
See 2 more Smart Citations
“…At the end of the experiment, phenol was removed for 100.00 and 7.30% from the tests at the phenol concentrations of 10 and 100 mg/L, respectively. Some previous works found that bacterial cultures could use phenol as a growth substrate even up to concentrations of 10,000 mg/L [6], [9], [10]. In this study, based on the result of the test at the phenol concentration of 10 mg/L, it is clear that AS could degrade and use phenol as a sole carbon source similar to the previous work [6], [9], [10].…”
Section: A Potential Of Phenol Removal By Assupporting
confidence: 80%
“…Some previous works found that bacterial cultures could use phenol as a growth substrate even up to concentrations of 10,000 mg/L [6], [9], [10]. In this study, based on the result of the test at the phenol concentration of 10 mg/L, it is clear that AS could degrade and use phenol as a sole carbon source similar to the previous work [6], [9], [10]. Additionally, some previous works reported phenol adsorption ability of AS [11], [12].…”
Section: A Potential Of Phenol Removal By Asmentioning
confidence: 99%
See 1 more Smart Citation
“…cell leakage and metabolite exchange. The increased production of Daptomycin in immobilized system over free cells is accounted due to changes in permeability of cell wall as well as reusability of the matrices 15 . Immobilization capacity, time for immobilization, Daptomycin production with immobilized biomass and finally mechanical stability of the carrier are the key factors to be noted.…”
Section: Fig 5: Sem Analysis Of Immobilized Cells On (A) Refractory mentioning
confidence: 99%
“…(Adav et al 2007;Jiang et al 2013), Bacillus spp. (Banerjee and Ghoshal 2010;Kuang et al 2013) and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%